دراسة الخواص الفيزيائية لأكسيد النيكل (NiO) - حلبي, محمد (Latakia University Journal -Basic Sciences Series, 2018)
ضُغط مركب أ كسيد النيكل (NiO)على هيئة قرص وحُرق لمدة ساعتين داخل فرن كهربائي عند درجة حرارة (1200). تتناول هذه الدراسة قياس كل من المقاومة النوعية وثابت العزل الكهربائي والناقلية الحرارية والجهد الكهروحراري. لاحظنا من المنحني المعبر عن سلوك المقاومة النوعية مع درجة الحرارة وجود ثلاث قيم لطاقة التنشيط Eg )). أيضًا تزايد الناقلية الحرارية وثابت العزل الكهربائي مع ازدياد درجة الحرارة. تأتي أهمية مركب أكسيد النيكل (NiO) من تطبيقاته العديدة وأهمها استخدامه كمجس لتقدير كمية الحرارة. Nickel oxide was pressed into disc, and burned at (1200) inside electric furnace for two hours. This study shows the measurement of the electric resistivity, dielectric constant, thermal conductivity and pyro-electric voltage. We noticed three activation energies (Eg.) appeared. With the temperature behaviour of resistivity, the thermal conductivity and the dielectric constant increased as the temperature increases. The importance of (NiO) compound can be used as a sensor for detecting the amount of heats.